The clinico‐pathological characterisation of focal cortical dysplasia type IIb genetically defined by MTOR mosaicism. Issue 1 (10th January 2023) - Wang, Yajie; Yu, Tao; Blümcke, Ingmar; Cai, Yanning; Sun, Ke; Gao, Runshi; Wang, Yujiao; Fu, Yongjuan; Wang, Wei; Wang, Yuping; Zhang, Guojun; Piao, Yueshan
Abstract: Aims: Focal cortical dysplasia (FCD) is a major cause of drug‐resistant paediatric epilepsy and is amenable to successful neurosurgical resection. FCD ILAE Type IIb is the most common FCD subtype, and brain somatic mutations affecting the mTOR pathway play a major pathogenic role. The aim of this study was to comprehensively describe the genotype–phenotype association of 20 patients with histopathologically confirmed FCDIIb using next generation sequencing (NGS) of paired blood–brain samples. Methods: Clinical and neuropathological data were retrospectively reviewed from the hospital archive. The NGS panel included 11 mTOR‐pathway‐related genes with maximum coverage of 2000×. The detected variants were validated by digital droplet PCR. Results: Pathogenic MTOR variants were identified in 10 patients (50%). Further comparison with MTOR ‐wildtype FCDIIb suggested a profound genotype–phenotype association characterised by (1) a non‐temporal lobe lesion on MRI, (2) a larger lesion volume occupying grey and white matter (3.032 ± 1.859 cm 3 vs 1.110 ± 0.856 cm 3, p  = 0.014), (3) more balloon cells (50.20 ± 14.40 BC/mm 2 vs 31.64 ± 30.56 BC/mm 2, p  = 0.099) and dysmorphic neurons (48.72 ± 19.47DN/mm 2 vs 15.28 ± 13.95DN/mm 2, p  = 0.000) and (4) a positive correlation between VAF and the lesion volume ( r  = 0.802, p  = 0.017). Conclusions: Our study identified frequent MTOR mutations in the cell‐rich FCDIIb phenotype, clinically characterised by a non‐temporal location and large lesion volume. Comprehensive genotype–phenotype associations will help us further explore and define the broad spectrum of FCD lesions to make more targeted therapies available in the realm of epileptology. Abstract : Targeted hybrid capture next generation sequencing of a panel including 11 mTOR‐pathway related genes identified pathogenic somatic MTOR variants in 10/20 FCDIIb patients, all of which revealed a profound clinical and pathological phenotype characterised by (1) a non‐temporal lobe lesion on MRI, (2) a large lesion volume, (3) abundant balloon cells and dysmorphic neurons visible in the resected brain sample and (4) variant allele frequency (VAF) correlated with the extent of the epileptogenic zone.